Case study of flow instabilities in subchannels via multidimensional CFD approach. (May 2023) - Long, Jianping; Yang, Baowen; Zhang, Bin; Wang, Sipeng
Highlights: Multi dimensions simulations on two phase flow instabilities in rod bundle subchannels based on a two-fluid CFD approach were conducted. Three dimensional effects caused by cross flow (including mass, momentum, and energy transfer between channels) between channels (multidimensional mixing effects between channels) on flow instability in rod bundle subchannels were revealed. Transient three dimensional distributions of key thermal hydraulic parameters rod bundle subchannels during flow instability were obtained. Abstract: Multidimensional simulations on two-phase flow instabilities based on a two-fluid CFD approach with water as working fluid were conducted for upward flow in both single subchannel and 2 × 1 subchannels at 4.5 MPa. During the simulations, the inlet subcooling was set to 10 K, 15 K, and 20 K respectively. The subchannel is 1060 mm in length with a rod wall pitch by rod diameter (P/D) of 12.6 mm/9.5 mm. Simulations were performed by fixing the pressure inlet and outlet boundary conditions and increasing the heat flux to reach flow instability conditions. The results showed that the CFD approach successfully simulated the flow instability phenomena. In the case of flow instability, the flow and heat transfer characteristics changed greatly, which resulted in rising temperature and further early CHF. This paper reveals the open connectivity structure in the subchannel system enhanced the stability of the two-phase flow system compared with one-dimensional simulation due to the multidimensional mixing effects between channels captured by CFD approach.